2019
DOI: 10.3390/polym11081312
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Controlled Solvent Vapor Annealing of Thin Block Copolymer Films

Abstract: Solvent vapor annealing is as an effective and versatile alternative to thermal annealing to equilibrate and control the assembly of polymer chains in thin films. Here, we present scientific and practical aspects of the solvent vapor annealing method, including the discussion of such factors as non-equilibrium conformational states and chain dynamics in thin films in the presence of solvent. Homopolymer and block copolymer films have been used in model studies to evaluate the robustness and the reproducibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 98 publications
(154 reference statements)
0
35
0
Order By: Relevance
“…A standardised methodology for polymer based lithographic techniques that has effective defect control, effective pattern transfer and flexible nanopatterning is critical [ 10 , 138 ]. Defect mitigation and repair techniques are under development as they are simple, consisting of basic apparatus for pressure and temperature control [ 123 , 124 ].…”
Section: Bottom-up Versus Top-down Lithographymentioning
confidence: 99%
See 2 more Smart Citations
“…A standardised methodology for polymer based lithographic techniques that has effective defect control, effective pattern transfer and flexible nanopatterning is critical [ 10 , 138 ]. Defect mitigation and repair techniques are under development as they are simple, consisting of basic apparatus for pressure and temperature control [ 123 , 124 ].…”
Section: Bottom-up Versus Top-down Lithographymentioning
confidence: 99%
“…Ionic liquids (ILs) can also be environmentally friendly if chosen carefully [122]. Development of an industrial SVA system that is fast and precise, with potential for wafer scale processing, will help facilitate the transition of this technology from the research scale to the industrial [123][124][125]. Annealing chambers with temperature and gas flow systems facilitate thickness and pattern formation control [124,125].…”
Section: Polymer-based Pattern Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Toluene and chloroform are commonly used solvents for both PSPVP BCP deposition and SVA. 45,46,47,48,49 However, toluene (vapor pressure = 3.78 kPa @ 25°C) and chloroform (vapor pressure = 25.12 kPa @ 25°C) are volatile solvents (although chloroform is markedly more volatile than toluene) in comparison to PGMEA (vapor pressure = 0.50 kPa @ 25°C) and can therefore lead to film instability or kinetically trapped micellar structures. As discussed earlier, this is especially true with respect to films cast from toluene since toluene is a PS favorable solvent.…”
Section: Surface Functionalization and Block Copolymer Film Preparationmentioning
confidence: 99%
“…A similar approach is demonstrated on vapor-annealed thin films of a PS-b-PEO diblock copolymer by Jin Xu et al [24], where the cylindrical PEO domains are loaded with iron and cobalt ions, followed by an oxidative and thermal treatment to yield regularly arranged, ferrimagnetic cobalt ferrite nanodots with suitable transition temperature to superparamagnetic nanodots, making them interesting candidates for memory storage applications. A systematic study of vapor annealing to equilibrate polystyrene-block-poly(2-vinylpyridine) diblock copolymer films and corresponding homopolymers using in situ spectroscopic ellipsometry and different microscopies is presented by Xiao Cheng et al, who found the temperatures of the substrate and the solvent vapor to be main controlling parameters influencing the dynamics of equilibration [25].…”
mentioning
confidence: 99%